Resource needs for adolescent friendly health services: estimates for 74 low- and middle-income countries. - Charlotte Deogan (Public Library of Science (PLoS), 2012)
Background In order to achieve Millennium Development Goals 4, 5 and 6, it is essential to address adolescents' health. Objective To estimate the additional resources required to scale up adolescent friendly health service interventions with the objective to reduce mortality and morbidity among individuals aged 10 to 19 years in 74 low- and middle- income countries. Methods A costing model was developed to estimate the financial resources needed to scale-up delivery of a set of interventions including contraception, maternity care, management of sexually transmitted infections, HIV testing and counseling, safe abortion services, HIV harm reduction, HIV care and treatment and care of injuries due to intimate partner physical and sexual violence. Financial costs were estimated for each intervention, country and year using a bottom-up ingredients approach, defining costs at different levels of delivery (i.e., community, health centre, and hospital level). Programme activity costs to improve quality of care were also estimated, including activities undertaken at national-, district- and facility level in order to improve adolescents' use of health services (i.e., to render health services adolescent friendly). Results Costs of achieving universal coverage are estimated at an additional US$ 15.41 billion for the period 2011-2015, increasing from US$ 1.86 billion in 2011 to US$ 4,31 billion in 2015. This corresponds to approximately US$ 1.02 per adolescent in 2011, increasing to 4.70 in 2015. On average, for all 74 countries, an annual additional expenditure per capita ranging from of US$ 0.38 in 2011 to US$ 0.82 in 2015, would be required to support the scale-up of key adolescent friendly health services. Conclusion The estimated costs show a substantial investment gap and are indicative of the additional investments required to scale up health service delivery to adolescents towards universal coverage by 2015.